Cervical Intraepithelial Neoplasia Is Associated With Genital Tract Mucosal Inflammation - Mhatre, Mohak (2012)
BACKGROUND: Clinical studies demonstrate increased prevalence of human papillomavirus (HPV)-associated disease in HIV-infected individuals and an increased risk of HIV acquisition in HPV-infected individuals. The mechanisms underlying this synergy are not defined. We hypothesize that women with cervical intraepithelial neoplasia (CIN) will exhibit changes in soluble mucosal immunity that may promote HPV persistence and facilitate HIV infection. METHODS: The concentrations of immune mediators and endogenous anti-Escherichia coli activity in genital tract secretions collected by cervicovaginal lavage were compared in HIV-negative women with high-risk HPV-positive (HRHPV+) CIN-3 (n = 37), HRHPV+ CIN-1 (n = 12), or PAP-negative control subjects (n = 57). RESULTS: Compared with control subjects, women with CIN-3 or CIN-1 displayed significantly higher levels of proinflammatory cytokines including interleukin (IL)-1α, IL-1β, and IL-8 (P < 0.002) and significantly lower levels of anti-inflammatory mediators and antimicrobial peptides, including IL-1 receptor antagonist, secretory leukocyte protease inhibitor (P < 0.01), and human β defensins 2 and 3 (P < 0.02). There was no significant difference in endogenous anti-E. coli activity after controlling for age and sample storage time. CONCLUSION: HRHPV+ CIN is characterized by changes in soluble mucosal immunity that could contribute to HPV persistence. The observed mucosal inflammation suggests a mechanism that may also contribute to the epidemiologic link between persistent HPV and HIV.